Impact of adherence to antiemetic guidelines on the incidence of chemotherapy-induced nausea and vomiting and quality of life - DANE, FAYSAL; SANCAR, MESUT (SPRINGER, 2016)
Background International guidelines are tools enabling physicians to incorporate the latest evidence based clinical information into practice. Objective This study aimed to evaluate the impact of antiemetic guidelines adherence on the incidence of chemotherapy-induced nausea and vomiting (CINV) and patient quality of life. Setting Marmara University Pendik Training and Research Hospital chemotherapy unit, Istanbul, Turkey. Method The study included 100 chemotherapy naive patients. Antiemetic prescribing patterns and their consistency with MASCC/ESMO 2014 guidelines were assessed. Patients recorded incidences of vomiting in a daily dairy and described their nausea using a 7-item Likert Scale. The incidence of CINV was recorded over five days. To assess the patient's quality of life, a modified Turkish version of the Functional Living Index-Emesis (FLIE) questionnaire was administered before and after receiving chemotherapy. A questionnaire on the existence and severity of side effects was developed and administered. Main outcome measures Incidence of side effects on CINV and quality of life according to the FLIE. Results The primary outcome revealed differences in complete control (no emetic episodes, rescue therapy or nausea), FLIE scores and side effects. Guidelines consistency was observed more with acute (A) than with delayed (D) prevention of CINV, with significant differences in complete control between the guideline adherent group (GAG) and the guideline nonadherent group (GNG). Significant differences in the FLIE score were noticed between GAG(D) and GNG(D), and GNG(D) had a higher incidence of diarrhoea, headache, swallowing difficulties and dark-coloured stool. Conclusion Consistency with guidelines resulted in significant reduction in the incidence of both cute and delayed CINV and other side effects, and with improvement of the patient quality of life.
Keywords: Adverse drug reaction; Chemotherapy; Guideline; Nausea; Quality of life; Vomiting; MODERATELY EMETOGENIC CHEMOTHERAPY; RECEPTOR ANTAGONIST APREPITANT; PLACEBO-CONTROLLED TRIAL; INDUCED DELAYED EMESIS; DOUBLE-BLIND; CANCER-PATIENTS; PHASE-III; PLUS DEXAMETHASONE; ONDANSETRON; CISPLATIN